Sobre o currículo escolar para John Dewey: uma leitura a partir de algumas obras - Santos, Thais Figueiredo (2011)
This research, which can be called as a literature review, has as its intention: to present the curriculum from different theoretical perspectives, discussing their intersections with knowledge, experience and democracy, to examine how the curriculum is discussed on Dewey's theory, and if there are similarities between John Dewey's ideas and conceptions of contemporary theorists of Curriculum Studies, based on the following question: How did John Dewey think the curriculum in his time, and how can we re-contextualize their ideas to think about curriculum today? It has studied the works Dewey published between the years of 1897-1902 (My Pedagogic Creed, The School and Society, and The Child and the Curriculum), a period that he put their philosophical and pedagogical ideas into practice in the Chicago Laboratory School. It was found that many of Dewey's ideas can be used to think the curriculum today, especially its relations with the educational experience, the school environment and Democracy.